Smart Camp: A Sustainable Digital Ecosystems Environment - Kohn, M.; Oslislo, L.; Talevski, Alex; Karduck, A. (IEEE, 2010)
Seamlessly integrating energy saving with the habits of daily life is an ambitious goal. It becomes even a bigger challenge in a remote area, like the Western-Australian Outback. Harsh environment, high temperatures and hard working conditions demand great exertion from humans and make one’s well-being an integral part of life. To bring both together – environmental sustainability and life quality – is a new interdisciplinary approach in the field of computer science. A “Smart Camp” is a new low rate wireless personal area network (LR-WPAN)-based solution, which provides accommodations in a remote mining site with a smart automation and information system to contribute toenvironmental sustainability and to provide amenities for its inhabitants. The Smart Camp intends to monitor and control household appliances with the aim to reduce the overall energy consumption. Additionally, multi-media components will be implemented, which aim to make the occupants life more pleasant by adding value to their habitat.